An active heteropolysaccharide from the rinds of Garcinia mangostana Linn.: Structural characterization and immunomodulation activity evaluation. (1st May 2020) - Zhang, Shaojie; An, Lijun; Li, Zhengguo; Wang, Honglin; Shi, Lijuan; Zhang, Jie; Li, Yuhao; Jin, Da-Qing; Tuerhong, Muhetaer; Ohizumi, Yasushi; Shuai, Ling; Xu, Jing; et al.
Graphical abstract: Highlights: An active heteropolysaccharide, GMP70-1, was isolated from G. mangostana for the first time. The structure and morphology of GMP70-1 were characterized for the first time. GMP70-1 was shown to have a single-helix structure. GMP70-1 significantly enhanced the phagocytosis and the secretion of cytokine of RAW264.7 cells. An in vivo zebrafish screening confirmed GMP70-1 to have immunomodulatory effects. Abstract: A previously undescribed polysaccharide, GMP70-1, was isolated from the rinds of Garcinia mangostana Lin. Physicochemical characterization analysis showed that GMP70-1 (absolute molecular weight: 2.01 × 10 4 g/mol) is a multi-branched acidic heteropolysaccharide with a compact coil chain conformation in sodium chloride solution. The repeated unit of GMP70-1 was mainly composed of (1 → 5)-linked α -L-Ara f, (1 → 3, 5)-linked α -L-Ara f, (1 → 2, 4)-linked α -L-Rha p, (1 → 4)-linked β -D-Gal p, terminating with t- α -L-Ara f, t- α -D-Gal p A, and t- β -D-Gal p . To explore the medicinal potential responsible for the bioactivity of G. mangostana, an immunomodulatory assay was performed. The in vitro cell test showed that GMP70-1 possessed a prominent immunoregulatory activity by enhancing the phagocytic uptake of neutral red and promoting the secretion of nitric oxide (NO), reactive oxygen species (ROS), tumor necrosis factor- α (TNF- α ), interleukin (IL)-6, and IL-1 β of macrophages. Furthermore, an in vivo zebrafish evaluation revealed that the production of ROS and NO was significantly increased after treated with GMP70-1.